A novel device for the endoscopic management of buried bumper syndrome - Hindryckx, Pieter; Dhooghe, Barbara; Wannhoff, Andreas (Endoscopy, 2019)
Background Buried bumper syndrome (BBS) is a complication of percutaneous endoscopic gastrostomy (PEG) in which the internal bumper is overgrown by the gastric mucosa. Apart from loss of patency of the PEG tube, the buried bumper may evoke symptoms such as abdominal pain or peritubular leakage. While the management of an incompletely buried bumper is fairly straightforward, this is not the case for a completely buried bumper. Different approaches to remove completely buried bumpers have been described, including endoscopic knife- or papillotome-based techniques. However, these devices are used off-label and the procedures can be laborious.Methods The Flamingo device has recently been introduced as the first tool specifically designed to remove a completely buried bumper.Results We describe the technique and our first experience in five patients with a completely (n = 4) or almost completely (n = 1) buried bumper. Fast and save removal of the buried bumper was obtained in all patients.Conclusion We believe that this device has the potential to become the standard first-line tool for the management of completely buried bumpers.